Kunskapsbildning för professionellt lärande genom kollegiala samtal - Jaana Nehez; Katina Thelin; Veronica Sülau; Eva Kane; Karin Rönnerman (Dalarna university, 2024)
Professional learning based on collegial conversations is an issue worldwide. However, there is a need for deeper knowledge about what happens in such conversations. Based on practice theories and theories of knowledge building environments, this article explores collegial conversations among teachers and school leaders. The findings show three conversation practices that can be of importance in professional learning, although not always in terms of knowledge building discourse moves: knowledge building practices, disrupted knowledge building practices and non-knowledge building practices. The latter two include significant relational aspects. The conclusion is that we need to widen the understanding of knowledge building to achieve professional learning.